2019
DOI: 10.3390/en12081575
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling and Simulation of Nanoparticle-Assisted Enhanced Oil Recovery—A Review

Abstract: In the last two decades, nanotechnology has flourished due to its vast number of applications in many fields such as drug delivery, oil and gas, and thermal applications, like cooling and air-conditioning. This study focuses on the applications of nanoparticles/nanofluids in the Enhanced Oil Recovery (EOR) process to increase oil recovery efficiency. To understand the nanoparticle-assisted EOR process, the first step is to understand the flow characteristics of nanoparticles in porous media, including entrapme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…To enlarge the spectrum of the investigation, we decided to evaluate the environmental impact of barocaloric technology while the system mounts advanced HTF: The nanofluids [39][40][41][42][43][44][45]. Specifically, we tested variable concentrations of Al 2 O 3 -water nanofluids and of Cu-50%EG/50%W nanofluids, respectively, for heat-pumping and for cooling usages.…”
Section: Auxiliary Fluidsmentioning
confidence: 99%
“…To enlarge the spectrum of the investigation, we decided to evaluate the environmental impact of barocaloric technology while the system mounts advanced HTF: The nanofluids [39][40][41][42][43][44][45]. Specifically, we tested variable concentrations of Al 2 O 3 -water nanofluids and of Cu-50%EG/50%W nanofluids, respectively, for heat-pumping and for cooling usages.…”
Section: Auxiliary Fluidsmentioning
confidence: 99%
“…The number of hidden neurons can be identified by employing a trial-and-error procedure [57,58] or using some empirical rules, as reported in [59]. There is no specific process to evaluate the optimal number of hidden neurons, but it must be identified case by case.…”
Section: Training the Artificial Neural Networkmentioning
confidence: 99%
“…Therefore, EM waves behave differently at different interfaces within the reservoir [5,6]. The propagating EM wave exerts forces on the molecules, which then align in a direction parallel to the external EM field [7][8][9]. Application of electromagnetic (EM) waves of certain frequency ranges has been used in nanofluid core flooding experiments for stimulating the recovery of residual oil after water flooding [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Application of electromagnetic (EM) waves of certain frequency ranges has been used in nanofluid core flooding experiments for stimulating the recovery of residual oil after water flooding [10][11][12][13][14]. The potential efficiency of this method has been demonstrated by several experimental and numerical studies [8,[15][16][17][18][19][20][21][22]. Different recovery mechanisms other than the common EM heating method have been reported recently.…”
Section: Introductionmentioning
confidence: 99%